POLICY RATES PASS-THROUGH IN INDONESIA’S DUAL BANKING SYSTEM: DOES BUSINESS CYCLE MATTER? - Sugeng Triwibowo; Defy Oktaviani; Adhitya Ginanjar; Danu F. Ardiansyah (Bank Indonesia, 2022)
This paper examines the pass-through of the policy rate to conventional and Islamic bank rates during the recessionary and expansionary episodes for the case of Indonesia. Applying an error-correction modelling to monthly data from June 2014 to April 2021, our findings confirm that the interest rate pass-through is sensitive to the business cycle for both conventional and Islamic banks. The policy rate pass-through to deposit rates is higher during the recession for both banking types. We also note that the lending rates of conventional banks fully adjust to the policy rate in the recessionary phase. The findings for Islamic financing rates are interesting. Namely, they tend to move inversely with the policy rates during the expansionary period. Meanwhile, depending on the rates, they are either over-responsive or less responsive during the recessionary phase. Finally, the degree of short-run adjustment in most banking rates is not influenced by the business cycle. These findings suggest that Islamic banking rates are less synchronized to the monetary policy rate, indicating that sharia-based banking barely supports counter-cyclical monetary policy.